Evaluating methodology and technology of sled tow studies in field sport athletes: a narrative review - Earnshaw, K. A.; Brughelli, M.; Uthoff, A. (The Journal of Sport and Exercise Science, 2022)
The use of resisted sled towing to enhance sprint capabilities has become one of the most common forms of training in the past decade due to its ability to develop phase-specific mechanical and muscular sprint capabilities. This increase in sled tow popularity has resulted in an abundance of literature that highlights the discrepancies around load prescription volume, intensity, and methodology. To date, sled tow reviews have focused on the usefulness of weighted sled towing as a form of resisted sprint training when in comparison to unresisted sprint training. The purpose of this review is to identify and discuss the different technologies and methodologies used to assess sled tow sprinting and their associated performance variables and provide practical considerations for coaches who wish to utilise these methods of training and sprint assessment. This review outlines current sled tow literature and methodological approaches, with an emphasis on how different technologies and application of methodology are used and how they affect outcome variables. Furthermore, the review aims to assist industry practitioners with their current understanding of resisted sled tow sprinting application, while highlighting a need for future research to streamline methodological approaches and develop technological advances to accurately measure and report acceleration phase variables.